2020
DOI: 10.1111/jfpp.14973
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different methods of mango drying assisted by a pulsed electric field on chemical and physical properties

Abstract: Mango fruit (Mangifera indica L.) belongs to the Anacardiaceae family (Barreto et al., 2008). Mango has a special economic position, due to its high nutritional value and rising consumer demand in the recent years. It is a great source of carbohydrates, vitamin A, B 1 , B 3 , B 5 , B 6, and C as well as β-carotene (Braga et al., 2019). However, of particular importance is the high content of polyphenols, including mangiferin, catechins, anthocyanins and many other, protecting the cells from free radical damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…As can be seen from Table 1, the degree of damage to the apple tissue through the application of electric pulses during the pre-treatment increased along with the increase in the amount of supplied energy (CDI ranged between 0.29-0.55). The obtained results correlate with previous published studies (Lammerskitten et al 2020;Shorstkii et al 2022).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As can be seen from Table 1, the degree of damage to the apple tissue through the application of electric pulses during the pre-treatment increased along with the increase in the amount of supplied energy (CDI ranged between 0.29-0.55). The obtained results correlate with previous published studies (Lammerskitten et al 2020;Shorstkii et al 2022).…”
Section: Resultssupporting
confidence: 92%
“…This accelerates the drying process and, thus, reduces the degradation of important bioactive compounds, e.g. flavonoids in mangoes (Lammerskitten et al 2020). The application of a pulsed electric field before vacuum drying also allowed the authors to increase the retention of β-carotene in the obtained dried carrot (Liu et al 2020a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the PEF parameters are not properly adjusted, too high energy delivered to the sample may contribute to “overtreatment” causing undesirable degradation of pigments. For instance, the TCC in convective dried mango increased from 90.4 mg/100 g dm (dry matter) for untreated material to 149.2 mg/100 g dm for PEF 1 kJ/kg and decreased to 43.4 mg/100 g dm for PEF 3 kJ/kg (Lammerskitten et al., 2020).…”
Section: Effect Of Nonthermal Treatment On Natural Food Pigments and ...mentioning
confidence: 99%
“…For instance, recently it has been demonstrated that PEF reduces the drying time of parsnips [37] and onions [38]. Moreover, the application of PEF can positively influence the quality of dry material, as was exemplified using mango [39]. In comparison with HPP, PEF is a cheaper method, and it can be applied using continuous modes.…”
Section: Introductionmentioning
confidence: 99%